Necrotic Cell Sensor Clec4e Promotes a Proatherogenic Macrophage Phenotype Through Activation of the Unfolded Protein Response. Issue 14 (4th October 2016) - Clément, Marc; Basatemur, Gemma; Masters, Leanne; Baker, Lauren; Bruneval, Patrick; Iwawaki, Takao; Kneilling, Manfred; Yamasaki, Sho; Goodall, Jane; Mallat, Ziad
Abstract : Background: Atherosclerotic lesion expansion is characterized by the development of a lipid-rich necrotic core known to be associated with the occurrence of complications. Abnormal lipid handling, inflammation, and alteration of cell survival or proliferation contribute to necrotic core formation, but the molecular mechanisms involved in this process are not properly understood. C-type lectin receptor 4e (Clec4e) recognizes the cord factor of Mycobacterium tuberculosis but also senses molecular patterns released by necrotic cells and drives inflammation. Methods: We hypothesized that activation of Clec4e signaling by necrosis is causally involved in atherogenesis. We addressed the impact of Clec4e activation on macrophage functions in vitro and on the development of atherosclerosis using low-density lipoprotein receptor–deficient ( Ldlr −/− ) mice in vivo. Results: We show that Clec4e is expressed within human and mouse atherosclerotic lesions and is activated by necrotic lesion extracts. Clec4e signaling in macrophages inhibits cholesterol efflux and induces a Syk-mediated endoplasmic reticulum stress response, leading to the induction of proinflammatory mediators and growth factors. Chop and Ire1a deficiencies significantly limit Clec4e-dependent effects, whereas Atf3 deficiency aggravates Clec4e-mediated inflammation and alteration of cholesterol efflux. Repopulation of Ldlr −/− mice with Clec4e −/− bone marrow reduces lipid accumulation, endoplasmic reticulum stress, and macrophage inflammation and proliferation within the developing arterial lesions and significantly limits atherosclerosis. Conclusions: Our results identify a nonredundant role for Clec4e in coordinating major biological pathways involved in atherosclerosis and suggest that it may play similar roles in other chronic inflammatory diseases. Abstract : Supplemental Digital Content is available in the text.